The impact of music-imaginative pain treatment (MIPT) on psychophysical affect regulation – A single case study - Glomb, Sina; Böckelmann, Irina; Frommer, Jörg; Metzner, Susanne (Frontiers in Pain Research, 2022)
Music-imaginative Pain Treatment (MIPT) is part of the multi-professional treatment plan for hospitalised patients in departments for psychosomatic medicine. MIPT is an intervention that encourages the patient to create music representing pain and relief from pain and promotes active engagement and self-reflection. This single case study of a 46-year-old female patient diagnosed with chronic pain disorder with somatic and psychological factors includes narrative, demographic, psychometric, and cardiophysiological data. During the interventions, early childhood stress, which is a risk factor for developing chronic pain, turns out to be a crucial focal point in therapy and conspicuous in her handling of the music. Social trauma is considered an appropriate concept for a deeper understanding of the case.